TANTANGAN DAN PELUANG ANGKATAN KERJA TERDIDIK DI DUNIA KERJA UNTUK MENGATASI PERMASALAHAN PENGANGGURAN DI INDONESIA - Istiqomah Dzikrullah; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
The number of unemployed people in Indonesia is increasing day by day. And the number of productive age population in Indonesia is getting bigger and it is feared that the number of unemployment will also increase. Education plays a very important role for a labor force, because education can help improve the quality and competition of human resources in the world of work. Therefore, nowadays people are required to be highly educated because many job vacancies require educated workers. This is supported by the large number of university graduates. Unemployment in productive age has an impact on the high number of educated labor force who become unemployed or in other words, educated unemployment. This research aims to understand the challenges faced and opportunities for the educated labor force in overcoming the unemployment problem in Indonesia. By knowing the population, the level of education of a person and the number of the existing labor force, it is hoped that it can be understood how the educated labor force can face the problem of unemployment. This research uses the literature review method which contains reviews, summaries, and the author's thoughts about some literature.